2019
DOI: 10.1177/2054358119828388
|View full text |Cite
|
Sign up to set email alerts
|

Central Blood Pressure and Pulse Wave Velocity Changes Post Renal Denervation in Patients With Stages 3 and 4 Chronic Kidney Disease: The Regina RDN Study

Abstract: Background:Central aortic blood pressures and arterial stiffness are better indicators of cardiovascular outcomes than brachial blood pressures. However, their response to renal denervation (RDN) in patients with Stage 3 and Stage 4 chronic kidney disease (CKD) has not yet been examined.Objective:To evaluate the impact of RDN on central blood pressures (CBP), brachial (office and ambulatory) blood pressures, arterial stiffness, glomerular filtration rate (GFR), 24-hour urine protein, and selective cardiac para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…There were concerns of possible renal artery stenosis or compromised kidney function especially in patients with underlying CKD after renal denervation. Studies by Hering et al and Prasad et al on patients with CKD stage 3–4 found no significant alterations in kidney function after renal denervation until 12 and 24 months follow‐up, respectively 31,32 . There was no reported decline in eGFR or significant renal issues observed in the included studies in patients who underwent RSDN.…”
Section: Discussionmentioning
confidence: 74%
“…There were concerns of possible renal artery stenosis or compromised kidney function especially in patients with underlying CKD after renal denervation. Studies by Hering et al and Prasad et al on patients with CKD stage 3–4 found no significant alterations in kidney function after renal denervation until 12 and 24 months follow‐up, respectively 31,32 . There was no reported decline in eGFR or significant renal issues observed in the included studies in patients who underwent RSDN.…”
Section: Discussionmentioning
confidence: 74%
“…Of the 35 studies included in the full-text evaluation, seven were excluded because they were case reports, three were excluded because of the study protocol, two were excluded for insufficient data, two were excluded for duplicate patient data, and 10 did not meet the inclusion criteria. Finally, 11 single-center, non-randomized, uncontrolled studies were included in the meta-analysis (Figure 1) [18][19][20][21][22][23][24][25][26][27][28]. These 11 studies included 238 patients and are summarized in Table 1.…”
Section: Included Studiesmentioning
confidence: 99%
“…As shown in Table 4, two articles reported eGFR values at 1 month [21,23], four articles reported eGFR values at 3 months and 6 months [18,21,23,27], three articles reported eGFR values at 12 months [20,21,27], and two articles reported eGFR values at 24 months after RDN [21,27]. The heterogeneity among the studies was significant; therefore, the random-effects model was used for the analysis (Table 4).…”
Section: Renal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a nonrandomized renal-denervation intervention in patients with existing CKD, kidney function appeared stable when followed for the next 2 years (17). In the Global SYM-PLICITY Registry, with enrollment currently at about 2600 people who have undergone a radiofrequency ablation in the renal artery, no significant safety signal in terms of renovascular anatomy (i.e., unanticipated renal artery stenosis) or greater-than-expected kidney function decline has been noted.…”
Section: Point 2: Device-based Interventions Have a Reasonable Safetymentioning
confidence: 99%